2021
DOI: 10.3389/fphar.2020.628438
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mechanical Allodynia and Skin Innervation in a Mouse Model of Type-2 Diabetes Induced by Cafeteria-Style Diet and Low-Doses of Streptozotocin

Abstract: Background: Painful distal symmetrical polyneuropathy (DPN) is a frequent complication of type-2 diabetes mellitus (T2DM) that commonly presents as neuropathic pain and loss of skin nerve fibers. However, there are limited therapies to effectively treat DPN and many of the current animal models of T2DM-induced DPN do not appear to mirror the human disease. Thus, we validated a DPN mouse model induced by a cafeteria-style diet plus low-doses of streptozotocin (STZ).Methods: Female C57BL/6J mice were fed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It is possible that the initial phase of hypersensitivity was not replicated in these studies due to the acute period of T2DM induction. In contrast to the absence of hypoesthesia in female mice in this study, another study reported long-term allodynia using the same T2DM induction protocol as this study, although their study examined female C57BL/6 mice (Castañeda-Corral et al, 2021).…”
Section: Discussionmentioning
confidence: 65%
“…It is possible that the initial phase of hypersensitivity was not replicated in these studies due to the acute period of T2DM induction. In contrast to the absence of hypoesthesia in female mice in this study, another study reported long-term allodynia using the same T2DM induction protocol as this study, although their study examined female C57BL/6 mice (Castañeda-Corral et al, 2021).…”
Section: Discussionmentioning
confidence: 65%
“…The doses were selected based on those used in previous studies on pregabalin (Bardin et al, 2010;Chen et al, 2001;Eutamene et al, 2000;Goncalves & Dickenson, 2012;Kiso et al, 2008;Peng et al, 2012), duloxetine (Bardin et al, 2010;Iyengar et al, 2004;Kiso et al, 2008) and diclofenac (Granados-Soto et al, 2004;Khan et al, 2018;Sukriti & Pandhi, 2004). However, we cannot rule out the possibility that different doses could produce different results, specifically in the case of diclofenac as varied doses were used in other studies (Allchorne et al, 2012;Castaneda-Corral et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, chronic pain has also been investigated in metabolic disorder neuropathies [ 52 , 53 ]. Preclinical models of chronic pain induced by metabolic disorder neuropathies are based on chemical and surgical approaches, genetic, and diet alterations.…”
Section: Sexual Dimorphism Of Pain In Pre-clinical Studiesmentioning
confidence: 99%